Targeted therapeutic hypothermia protects against noise induced hearing loss - Rincon Sabatino, Samantha; Rivero, Andrea; Sangaletti, Rachele; Dietrich, W. Dalton; Hoffer, Michael E.; King, Curtis S.; Rajguru, Suhrud M. (Frontiers in Neuroscience, 2024)
Exposure to occupational or recreational loud noise activates multiple biological regulatory circuits and damages the cochlea, causing permanent changes in hearing sensitivity. Currently, no effective clinical therapy is available for the treatment or mitigation of noise-induced hearing loss (NIHL).Here, we describe an application of localized and non-invasive therapeutic hypothermia and targeted temperature management of the inner ear to prevent NIHL. We developed a custom-designed cooling neck collar to reduce the temperature of the inner ear by 3-4ºC post-injury to deliver mild therapeutic hypothermia. This localized and non-invasive therapeutic hypothermia successfully mitigated NIHL in rats. Our results show that mild hypothermia can be applied quickly and safely to the inner ear following noise exposure. We show that localized hypothermia after NIHL preserves residual hearing and rescues noise-induced synaptopathy over a period of months. This study establishes a minimallyinvasive therapeutic paradigm with a high potential for rapid translation to the clinic for long-term preservation of hearing health.